Noninvasive Diagnosis of Hepatocellular Carcinoma in Cirrhotic Liver: Current Guidelines and Future Prospects for Radiological Imaging - Ricke, Jens (S. Karger AG, 2012)
Noninvasive imaging has become the standard for hepatocellular carcinoma (HCC) diagnosis in cirrhotic patients. Typical imaging features of HCC such as arterial wash-in and venous wash-out deliver very high specificity and acceptable sensitivity even in nodules from 1 to 2 cm in diameter. However, limitations apply specifically in hypovascular HCC, for which the addition of new techniques such as diffusion-weighted magnetic resonance imaging (DW-MRI) or hepatobiliary MRI is helpful. Whereas DW-MRI adds to both the sensitivity and specificity, hepatobiliary MRI additionally contributes valuable information in cirrhotic patients on the histopathology of small lesions, including early HCC and high-grade dysplastic nodules. Biopsy of small, atypical lesions is associated with a high rate of false-negative findings and should be used only after careful consideration in selected patients. Here, we review the current international guidelines on HCC diagnosis as well as the latest developments in imaging that may contribute to safe detection and accurate characterization of suspicious nodules in patients with liver cirrhosis.